The novel time-dependent multimode self-consistent nonlinear theory of gyrotron - Kai Jia; Xinjian Niu; Yinghui Liu; Jianwei Liu; Zongzheng Sun; Hongfu Li (AIP Advances)
How to quickly and accurately analyze the effect of different modes competing with each other on the beam–wave interaction is an important question in developing gyrotrons. In this paper, a novel time-dependent multimode self-consistent nonlinear theory model is presented to research the mode competition phenomenon in high-frequency structures. This model investigates the electromagnetic field in the resonant cavity using generalized telegrapher’s equations to speed up the computational speed, adopts the waveguide-centered coordinate to represent the electron equations of motion to obtain realistic electron trajectories, and gives the form of the discretized representation of the source term under present conditions. Based on the theoretical model, we have developed the in-house code CESG-2024 to study gyrotron devices. Ultimately, we study the mode competition in a 95 GHz gyrotron utilizing this code, and the simulation results concord with the experimental results, further indicating the theory’s reliability.